Obesidade, capacidade funcional e nível de atividade física em idosos comunitários de Belo Horizonte e Diamantina - Esther Kévle Moreira de Lima (2017)
Brazil, a developing country, goes through the nutritional transition processes that increase the number of obese people. Aging itself already potentiates the storage of adipose tissue and obesity in old age behaves paradoxically, time as a protection factor, time as a risk factor. The way obesity can be associated with the aging process demands research, as this association is apparently complex. Even the subcultures and social characteristics of each municipality may be related to obesity and how it interacts with the aging of each individual. On the other hand, functional capacity, reflecting the individual's autonomy and independence in carrying out its daily activities, is associated with extrinsic factors such as social factors, but also with intrinsic factors such as senescence or obesity itself. Physical activity, in turn, helps to prevent comorbidities and improve the efficiency of the cardiorespiratory system that may or may not be associated with obesity and/or external factors, such as the difference in behavior between municipalities due to the subculture. In order to investigate obesity and the possible association with functional capacity and level of physical activity in the aging process in different municipalities, the study aimed to verify the proportion of obese people in the municipalities of Belo Horizonte and Diamantina and to compare the functional capacity and the level of physical activity with obesity in the community elderly according to the place they lived. Thus, the study was exploratory, observational, in which a process of active search and data collection was performed with obese and eutrophic elderly individuals, aged 60 years and over, community members, regardless of race or gender. The study protocol consisted on the application of a structured questionnaire that investigated social, economic and lifestyle issues, including energy expenditure through the Minnesota Leisure Time Activities Questionnaire (MLTAQ), body mass index (BMI) evaluation, waist circumference (WC), waist to hip ratio (WHR), and Incremental Shuttle Walking Test (ISWT) to assess participants' functional capacity. The study was carried out in two cities of Minas Gerais, southeastern region of the country, Belo Horizonte (BH) and Diamantina, with distinct socio-economic characteristics and urban profile. The normality of the data was verified through the Kolmogorov-Smirnov test and visual analysis of scatter plots. Comparison of functional capacity (ISWT), level of physical activity (MLTAQ), and anthropometric measures (WC and WHR) among municipalities and between obese and eutrophic was performed through Analysis of Variance (ANOVA) Two-way, with post hoc of Bonferroni. To compare the proportion of obese and non-obese elderly among the municipalities, the Chi-square test was used. In all tests, it were considered alpha of 5% and a 95% of confidence interval (CI). The results of the study showed that the level of physical activity was not different between the samples of the two municipalities or between the obese and eutrophic groups. Regarding global obesity, there was no difference in the proportion of obese elderly people among the municipalities. However, the indicators of central obesity, WC and WHR presented higher values in Diamantina, city with higher illiteracy rate and lower income, when compared to BH, city 100% urbanized and with lower human poverty index (HPI). The functional capacity, in turn, was higher in BH, when compared to Diamantina, since the sample had the highest average of the distance covered in the ISWT. However, there was no difference in functional capacity between obese and eutrophic elderly. The findings of the study did not show differences between obesity and the level of physical activity, but suggested that socioeconomic characteristics of the municipalities can influence the functional capacity of their respective elderly, since the city with lower income and schooling presented lower functional capacity, as well as greater accumulation of fat in the central region of the body.